2010
DOI: 10.1186/1471-2334-10-358
|View full text |Cite
|
Sign up to set email alerts
|

High levels of T lymphocyte activation in Leishmania-HIV-1 co-infected individuals despite low HIV viral load

Abstract: BackgroundConcomitant infections may influence HIV progression by causing chronic activation leading to decline in T-cell function. In the Americas, visceral (AVL) and tegumentary leishmaniasis (ATL) have emerged as important opportunistic infections in HIV-AIDS patients and both of those diseases have been implicated as potentially important co-factors in disease progression. We investigated whether leishmaniasis increases lymphocyte activation in HIV-1 co-infected patients. This might contribute to impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 34 publications
7
46
0
Order By: Relevance
“…Consistently, increased percentages of molecules associated with T cell activation, such as CD38 on CD8 + T cells and HLA-DR, are observed in VL/HIV patients compared to HIV/AIDS cases alone, and these molecules do not reach normal values despite undetectable viral load and clinical remission of leishmaniasis [46]. These molecules, especially those related to the risk of reactivation [47], also increase during VL relapse, suggesting that such molecules could be predictive of clinical outcome.…”
Section: Immunopathogenesismentioning
confidence: 82%
See 1 more Smart Citation
“…Consistently, increased percentages of molecules associated with T cell activation, such as CD38 on CD8 + T cells and HLA-DR, are observed in VL/HIV patients compared to HIV/AIDS cases alone, and these molecules do not reach normal values despite undetectable viral load and clinical remission of leishmaniasis [46]. These molecules, especially those related to the risk of reactivation [47], also increase during VL relapse, suggesting that such molecules could be predictive of clinical outcome.…”
Section: Immunopathogenesismentioning
confidence: 82%
“…One patient presented confluent, miliary papules on the face, thorax, and limbs, and the other presented non-pruritic and erythematous maculopapular lesions on the face and thorax [64], [65]. In two other patients [46], [66], the cutaneous lesion was concomitant to visceral involvement (erythematous papules and plaques). In one of these patients, the strain of Leishmania involved in the cutaneous lesions was L. donovani , which was confirmed by DNA sequence analysis [46].…”
Section: Clinical Aspectsmentioning
confidence: 95%
“…Similar to that observed for the CD4 + T counts, the viral or parasite antigens appear to act together to boost cell activation, either directly or by inducing the release of soluble factors. HIV-1 co-infection with other diseases, such as leishmaniasis (Santos-Oliveira et al 2010), tuberculosis (Rodrigues et al 2003) or leprosy (Giacoia-Gripp et al 2011), has previously been demonstrated to increase cellular activation. A previous study conducted in Mz did not identify a significant correlation between the "malaria infection" parameter and the levels of HLA-DR/CD38 on activated CD4 + and CD8 + T cells (Naniche et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Co-infection studies in primary human monocyte-derived MΦs, DCs, and tonsillar tissue demonstrated that each pathogen has a detrimental effect on containment of the other— Leishmania infection enhances HIV replication via chronic immune activation, and that HIV promotes Leishmania infection by suppressing a protective host defense [109112]. The latter is corroborated by higher levels of L. donovani parasitemia in HIV co-infected individuals [113] and low CD4 + T cell counts despite suppression of viral load by antiretroviral therapy [114]. …”
Section: Spectrum and Immunopathogenesis Of Progressive Vl In Humansmentioning
confidence: 99%